Penggunaan Media Audiovisual dalam Pembelajaran Menulis Teks Berita Siswa Kelas VII A SMPN 30 Muaro Jambi - Anggraini, Vica Nurista; Sulistiyo, Urip; Wini, Lusia Oktri (Jurnal Ilmiah Dikdaya, 2024)
The aim of this research is to describe how adiovisual media is used in learning to writee news texts for class VII A students at SMPN 30 Muaro Jambi. The approach used in this research is qualitative research with a case study type of research. The data colllection techniques used were pbservation, interviews, and documentation. The analiys techniques used are data collection, data reduction, data presentation, and drawing conclusions. The conclusion resuelt show that three is an influence on success in learning to write news texts using audiovisuals. With the existence of audiovisual media in the form of learning videos, students do not feel bored while learning. Student results showed that 11 students obtained an average score of 97 in the very good category.